Isolasi Dan Identifikasi Bakteri Proteolitik Dari Tanah Mangrove Di Pantai Pandaratan Kecamatan Sarudik Kabupaten Tapanuli Tengah - Linda Eriri; Rasyidah Rasyidah; Ulfayani Mayasari (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
Proteolytic bacteria are bacteria that can degrade proteins by producing extracellular protease enzymes. Proteolytic bacteria can be found in mangrove soil. This is because the dry weight of mangrove leaf litter contains 61% protein. The purpose of this study was to determine the presence of proteolytic bacterial isolates from mangrove soil in Pandaratan Beach, Sarudik District, Central Tapanuli Regency and to characterize them. This study used a laboratory experimental method which was analyzed descriptively. Soil sampling was carried out at two location points I (sandy) and location II (muddy) which were isolated using SMA media with the streak plate method. Characterization includes macroscopic and microscopic observations as well as biochemical tests. The results of the study found that there were 15 isolates of proteolytic bacteria isolated from the mangrove soil of Pandaratan Beach, Central Tapanuli. The highest activity test of the proteolytic index (IP) was obtained 0.82 mm by the Micrococcus (L1) and 0.09 mm lowest by Brevibacillus (L2). A total of 11 genera of proteolytic bacteria were found, including Curtobacterium (P1 and L7), Bacillus (P2, P4, and P7), Enterococcus (P3), Brevibacillus (P5 and L2), Carnobacterium (P6), Paenibacillus (P8), Micrococcus (L1), Vagococcus (L3), Marinococcus (L4), Halobacillus (L5), Sporosarcina (L6).